2015
DOI: 10.3390/vaccines3020320
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Adjuvants: from 1920 to 2015 and Beyond

Abstract: The concept of stimulating the body’s immune response is the basis underlying vaccination. Vaccines act by initiating the innate immune response and activating antigen presenting cells (APCs), thereby inducing a protective adaptive immune response to a pathogen antigen. Adjuvants are substances added to vaccines to enhance the immunogenicity of highly purified antigens that have insufficient immunostimulatory capabilities, and have been used in human vaccines for more than 90 years. While early adjuvants (alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
475
0
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(498 citation statements)
references
References 85 publications
(94 reference statements)
0
475
0
23
Order By: Relevance
“…In 1926, French veterinarian Gaston Ramon reported that by injecting starch, breadcrumbs, or tapioca, he managed to induce sterile abscesses at the site of injection with an inactivated toxin, which led to increased anti-sera production, confirming the hypothesis that substances able to induce local inflammation at the injection site were also able to enhance anti-sera yield (1). A few years later, British scientist Alexander Glenny discovered the immune-enhancing effects of aluminium salts (8).…”
Section: How Adjuvants Workmentioning
confidence: 96%
See 1 more Smart Citation
“…In 1926, French veterinarian Gaston Ramon reported that by injecting starch, breadcrumbs, or tapioca, he managed to induce sterile abscesses at the site of injection with an inactivated toxin, which led to increased anti-sera production, confirming the hypothesis that substances able to induce local inflammation at the injection site were also able to enhance anti-sera yield (1). A few years later, British scientist Alexander Glenny discovered the immune-enhancing effects of aluminium salts (8).…”
Section: How Adjuvants Workmentioning
confidence: 96%
“…Since the development of toxoid vaccines in the early 20 th century, scientists were searching for a way to enhance immunogenicity of non-living vaccines (1). Some of the first adjuvants discovered back then, on empirical basis of trial and error, are still in widespread use today, but only recently some light on the molecular mechanisms of their action has been shed.…”
Section: Introductionmentioning
confidence: 99%
“…30 Attempts have been made to use adjuvants to improve influenza vaccine immunogenicity, increase breadth of protection and enable antigen dose sparing, 31,32 with some of these adjuvanted vaccines having also been administered to pregnant women. Adjuvanted influenza vaccines currently available in Europe, contain MF59 Ò (Novartis) or AS03 (GlaxoSmithKline, GSK Biologicals) adjuvants.…”
Section: Adjuvanted Influenza Vaccines In Pregnancymentioning
confidence: 99%
“…Adjuvants act as immunopotentiators, increasing antigen presentation and improving the response to the vaccine ( Figure 1) [5]. In addition, adjuvants can be been used to improve immune responses in populations with conditions that cause an inadequate response to vaccination, as patients with renal disease [6].This topic is an important research field due to immunization with purified protein antigens typically results in the induction of a modest antibody response with little or no T cell response. Is necessary the search and development of new vaccine adjuvants for improve the protection against infectious diseases in humans and animals, this strategy should have the ability of prevent the infectious disease spread and zoonoses presence, improving the quality of life of the population [7].…”
Section: Introductionmentioning
confidence: 99%